Finite element analysis of Reinforced Concrete (RC) beams with continuously inclined shear reinforcement by using an equivalent constitutive property - Anandavalli, N.; Lakshmanan, N.; Iyer, Nagesh R.; Rajasankar, J.; Prakash, Amar (Journal of Structural Engineering, 2024)
Finite element (FE) analysis of reinforced concrete (RC) beams require concrete and steel to be modeled separately along with their interaction defined through either smeared, discrete or embedded approach. This is tedious and time consuming procedure. A simplified approach that considers RC as a homogenous material has been proposed earlier by the authors. In this paper, effectiveness of the approach to analyse RC beams with continuously inclined shear reinforcement is demonstrated. Equivalent constitutive property of RC beams is derived based on their momentcurvature relationship. Present approach significantly reduces the modeling effort and in turn, the computational demand. Displacement responses of four RC beams analysed using the equivalent constitutive property are compared with that of experimental values and are found be in good agreement.